SALDRU clippings collection : 1975-2000 (Southern Africa Labour & Development Research Unit, 2006)
A comprehensive reference resource containing 25 years of archival news clippings from English language newspapers in and around South Africa, digitized as .pdf files. There are over 1 million clippings, arranged into broad subject areas. The original clippings are now housed in the Liberation Archives at the University of Fort Hare.